Migratory strategies of juvenile northern fur seals (Callorhinus ursinus): bridging the gap between pups and adults - Zeppelin, Tonya (Sci Rep, 2019)
In species exhibiting differential migration by sex and age, understanding what differences exist, and the adaptive reasons for these differences is critical for determining how demographic groups will respond to environmental variability and anthropogenic perturbations. We used satellite-telemetered movement and diving data to investigate differential migration and its ontogeny in a highly migratory North Pacific Ocean predator, the northern fur seal (Callorhinus ursinus; NFS), with a focus on understudied juvenile (1- to 2-year-old) animals. We instrumented 71 juvenile NFS in two years (2006–07 and 2007–08) at three major North American breeding sites and compared their migratory strategies with pups and adults. Although sexual dimorphism is strong in adult NFS, only weak differences in body mass between sexes were found in juveniles, which had similar body mass to pups (~3–4 months). However, unlike widely-dispersed pups, juvenile male and female NFS dispersed in different directions, and used different habitats characterized by distinct hydrography and prey assemblages during migration, similar to breeding adults. Juvenile diving behavior differed only modestly among habitats and between sexes, consistent with weak differences in body mass. Evidence of habitat sexual segregation by juvenile NFS contradicts previous hypotheses that physiological differences predominantly drive the ontogeny of differential migration.